2020
DOI: 10.1101/2020.08.25.266692
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Local and substrate-specific S-palmitoylation determines subcellular localization of Gαo

Abstract: Peripheral membrane proteins (PMPs) associate with cellular membranes through post-translational modifications like S-palmitoylation. The Golgi apparatus is generally viewed as the transitory station where palmitoyl acyltransferases (PATs) modify PMPs, which are then transported to their ultimate destinations such as plasma membrane (PM); little substrate specificity among the many PATs has been determined. Here we describe inherent partitioning of Gαo – α-subunit of heterotrimeric Go-proteins – to PM and Golg… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 87 publications
(253 reference statements)
0
8
0
Order By: Relevance
“…The G203R, R209C, and E246K mutants show a similar dual localization (fig. S1, A to D), indicative of the normal posttranslational modifications of the mutants ( 20 ). Quantification of fluorescence intensities at the two compartments confirmed the near-equal distribution of wild-type Gα o and the three pathologic mutants (fig.…”
Section: Resultsmentioning
confidence: 99%
“…The G203R, R209C, and E246K mutants show a similar dual localization (fig. S1, A to D), indicative of the normal posttranslational modifications of the mutants ( 20 ). Quantification of fluorescence intensities at the two compartments confirmed the near-equal distribution of wild-type Gα o and the three pathologic mutants (fig.…”
Section: Resultsmentioning
confidence: 99%
“…The subcellular localization of three other Gαo pathological point mutants (Gly203Arg, Ile279Asn, and Asp174Gly) has been previously analyzed and found not to affect the plasma membrane localization [14], in contrast to what we see for the Gln52 mutants (Figure 4). It is worth noting that the retained Golgi localization of the Gln52 mutants is indicative of the proper lipid modifications of the Gln52 Gαo mutants [43].…”
Section: Discussionmentioning
confidence: 96%
“…When examining gene expression using the DropViz hippocampal single-cell RNAseq database, we found that 10 of the 30 palmitoylating/ de-palmitoylating enzymes and accessory proteins were predominantly enriched in neurons and also highly co-expressed with neuron-enriched differentially palmitoylated proteins from our screen. ZDHHC enzymes in this subset are thought to localize to a variety of subcellular domains, including the Golgi (ZDHHC3, ZDHHC13, ZDHHC17, ZDHHC21, ZDHHC23) and postsynapse (ZDHHC2, ZDHHC5, ZDHHC8) (Malgapo & Linder, 2021; Solis, Valnohova, Alvarez, & Katanaev, 2020). We found that a substantial proportion of the differentially palmitoylated substrates identified in our screen localize at the pre- and/or postsynapse, making ZDHHC2, ZDHHC5 and ZDHHC8 well positioned to mediate postsynaptic increases in substrate palmitoylation in response to plasticity-inducing stimuli.…”
Section: Discussionmentioning
confidence: 99%